Survey of The Physical Condition of Extracurricular Pencak Silat Students at Shofa Marwa Vocational School, Grobogan Regency (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
The purpose of this research is to determine the level of extracurricular physical condition of pencak silat at SMK Shofa Marwa, Grobogan Regency, this research method is a quantitative descriptive research used to analyze data by describing or describing data. The results of the research and discussion data can be concluded that the level of physical condition of pencak silat extracurricular athletes at SMK Shofa Marwa, Grobogan Regency in 2025 is classified as a medium category, the physical speed aspect is classified as a low category and the physical agility aspect of pencak silat extracurricular athletes at SMK Shofa Marwa, Grobogan Regency in 2025 is classified as very good.